Causes of Hoarseness of Voice Based on Fiber Optic Laryngoscopy (FOL): Our Experiences in ENT OPD of a Peripheral Military Hospital (Medicine Today, 2021)
Introduction: This study was aimed to determine the common causes of hoarseness of voice in ENT OPD of a military hospital.Materials and Methods: This was an observational study carried out on 93 patients presented with hoarseness of voice in ENT OPD CMH Momenshahi, a peripheral military hospital, for a period of 2 years, from 1st April 2017 to 30th April 2019. Only Fiber Optic Laryngoscopy (FOL) findings were evaluated to diagnose the causes of hoarseness. Data were obtained from FOL findings documentation register. All data were analyzed using IBM SPSS version 25.0. Patients consent was taken.Results: Total 93 cases were studied irrespective of age and sex. Among them 34 (36.60%) were males and 59 (63.40%) were females. Commonly affected age group was 21-30 years. With a mean age of 33.34 years. Majority of the cases were housewife 44 (44.10%). The most common cause of hoarseness was Chronic Laryngitis 25 (26.9%). The other causes were vocal polyp 17 (18.30%), VC nodule 13 (14%), Incomplete Glottal closure 14 (18.30%), leukoplakia of VC 5 (5.40%) and Vocal cord palsy 3 (3.20%). Normal findings were found in 11 (11.80%) cases.Conclusion: Hoarseness is a common symptom of laryngeal dysfunction. Military personnel are frequently affected like general population. Common causes are almost same with a very few variations. FOL should be the basic tool to diagnose the causes of hoarseness.Medicine Today 2021 Vol.33(1): 34-37